Roles of health promotion researchers in the planning stages of a global urban health promotion initiative: understandings identified from an interview-based case study - Sophie Meyer; Sophie Meyer; Nathalia González-Jaramillo; Annika Frahsa; Annika Frahsa (Frontiers in Public Health)
IntroductionHealth promotion research is marked by recognizing diverse forms of knowledge, the embeddedness of research practices in context, the relationship between researchers and stakeholders, and the articulation of knowledge production and sharing. Amid this epistemology, researchers’ understanding of their roles in specific projects and programs led by different stakeholders is essential. We used a global initiative to promote governance for health and wellbeing in five cities of different low-and middle-income countries as a case study to analyze senior-level researchers’ understanding of their role within the initiative.MethodsWe conducted a qualitative content analysis, supported by computer-assisted qualitative data analysis software, of verbatim interview transcripts from semi-structured qualitative interviews with the full sample of senior-level health promotion researchers (n = 5) who supported implementation of the initiative.ResultsWe identified three diverging types of local researchers’ roles understandings: (1) active deep involvement in collaborative arrangements, (2) balancing between active involvement and passively supporting, and (3) passively supporting the initiative. Researchers transcended sectoral boundaries to varying degrees and acted at the nexus between academic, practice, and policy communities.DiscussionOur proposed typology delineating the roles of senior-level health promotion researchers has the potential to stimulate reflexivity regarding role comprehension and underlying assumptions among all stakeholders before and during the implementation of ongoing and future urban health initiatives.